2009
DOI: 10.1007/s00432-009-0639-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of p53 as a surrogate marker for chemotherapeutical responsiveness in ovarian cancer

Abstract: In this study, the p53 mutational status was not predictive for responsiveness to platinum-based chemotherapy; but p53 was significantly more frequently mutated in poorly differentiated OCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…TP53 mutations detected by sequencing methods were found to be 57.5% in the study of Bauerschlag et al [13] and 73% in high-grade serous carcinoma in the study of Wong et al [19]. The mutation prevalences of the other studies are shown in Table 3.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…TP53 mutations detected by sequencing methods were found to be 57.5% in the study of Bauerschlag et al [13] and 73% in high-grade serous carcinoma in the study of Wong et al [19]. The mutation prevalences of the other studies are shown in Table 3.…”
Section: Resultsmentioning
confidence: 73%
“…The quality of the included papers ranged between good [14, 16, 17] and moderate [12, 13, 15, 18, 19]. Overall the articles were according to our research question and of fairly good quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations